Attitude Analysis in Taylor Swift’s Commencement Speech at New York University 2022 - Nur Mufidah; Widhiyanto Widhiyanto; Zulfa Sakhiyya (Green Publisher Indonesia, 2025)
This study examines how Attitude, as part of the Appraisal framework proposed by Martin and White (2005), is realized in Taylor Swift’s 2022 commencement speech at New York University. Through a qualitative descriptive approach, this research explores how the speaker uses evaluative language to construct interpersonal meaning and engage the audience. The focus is on the three sub-types of Attitude that are Affect, Judgment, and Appreciation, which correspond to expressions of emotion, evaluations of behavior, and assessments of phenomena, respectively. A total of 266 clauses from the speech were analyzed, with 172 identified as containing Attitude expressions. The findings show that positive Attitude overwhelmingly dominates the speech, especially through Affect, reflecting Swift’s strategy to foster empathy, motivation, and solidarity. Judgment is often used to present personal growth and moral insight, while Appreciation is employed to frame life experiences as meaningful. This study contributes to discourse analysis by highlighting how a non-traditional speaker like Taylor Swift constructs educational meaning through personal storytelling. It also demonstrates how celebrity speeches can fulfill the interpersonal and inspirational goals of academic ceremonies, offering a valuable case for Appraisal-based analysis in popular and educational discourse.